CYTOTOXICITY AND BIOACTIVITY OF GRAPE LEAVES EXTRACTS - PRITHA CHAKRABORTY; JERRIN SAM JOSEPH; THAHIYA NAUSHAD; JAYANTHI ABRAHAM (International Journal of Pharma and Bio Sciences, 2016)
Grapes belong to the Vitaceae family and scientifically known as Vitis vinifera. They are found to be rich in phenolics like resveratrol, anthocyanins, flavonoids. As the effect of grape leaves cytotoxicity is unexplored, the present work was aimed at evaluating the effect of extracts on cancer cell line and also on clinical pathogens. In this work, analytical study was done to identify compounds present in the methanol and aqueous extracts of grape leaves after phytochemical analysis. Antimicrobial activity of grape leaves was checked against nine clinical pathogens, namely Proteus mirabilis, Enterococcus sp., Salmonella sp., Shigella sp., Staphylococcus aureus, Serretia sp., Klebsiella sp., Pseudomonas aeuroginosa and Escherichia coli. Antioxidant property of grape leaves was studied by DPPH scavenging assay and cytotoxic effects were also checked against the MG63 cell line of osteocarcoma as bone cancer becomes an aggressive form of cancer. The Methanol extract showed better antimicrobial and antioxidant activity, where as both methanol and aqueous extract showed moderate anticancer activity. Grape leaves are suitable for further clinical approach in near future.